SHAKTI YOJANA: A SOCIOLOGICAL STUDY WITH SPECIAL REFERENCE TO KOPPAL, KARNATAKA - Dr. Venkatesh Naik R (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This study provides an analysis of the Shakti Yojana. Shakti Yojana is one of the major schemes of the Government of Karnataka, and this scheme is eligible for women of all castes, religions and classes, and the implementation of this scheme has helped in achieving the welfare of women. Therefore, it is important to understand the confusion caused by the implementation of the scheme and the government’s financial implications. To make this scheme successful, it is necessary to collect and analyse the suggestions of beneficiaries. For this reason, a study of the Free Bus Scheme, or Shakti Yojana, has been undertaken. For this study, information was collected through primary and secondary sources as well as through field study sources such as interview schedules and observations. To fulfil the objective of this research, 80 female beneficiaries of Koppal City were selected through simple random sampling. According to this study, 100% of the women saw a change in the financial condition of their families, and 100% of the women reduced their dependence on men. The study further observed that 75% of beneficiaries expressed the opinion that the government's financial insolvency and price rise are two factors that affect them.